Plato’s Cosmic Animal Vs. the Daoist Cosmic Plant: Religious and Ideological Implications - McDonough, Richard M. (Journal for the study of religions and ideologies, 2016)
Heidegger claims that it is the ultimate job of philosophy to preserve the force of the “elemental words” in which human beings express themselves. Many of these elemental words are found in the various cosmogonies that have informed cultural ideologies around the world. Two of these “elemental words,” which shape the ideologies (ethics, aesthetics, and religion of a culture) are the animal-model of the cosmos in Plato’s Timaeus and the mechanical models developed in the 17th-18th centuries in Europe. The paper argues that Daoism employs a third, and neglected, plant-model of cosmogony and of human life that provides an illuminating contrast to the other more well-known models. First, Plato’s animal-model of the cosmos and, second, the alternative Daoist plant-model of the cosmos are discussed. Third, the paper replies to the objection that the organic model in general and the plant-model in particular cannot accommodate human freedom. Fourth, it is shown how the Daoist plant-model supports a novel account of the central Daoist notion of wu-wei (doing nothing, but everything gets done). Fifth, the paper rebuts the objection that the Daoist plant-model of the cosmos and human life is fatally nihilistic. Sixth, the paper argues that the Daoist account of the origin of human religion, art and historical feeling cannot be properly understood apart from its plant-model of the cosmos and human life.